Simple and sensitive electrochemical detection of sunset yellow and Sudan I in food based on AuNPs/Zr-MOF-Graphene. (March 2023) - Sun, Ruimeng; Lv, Ruijuan; Li, Yuhan; Du, Ting; Chen, Lixia; Zhang, Yang; Zhang, Xiaoyu; Zhang, Lina; Ma, Hainan; Sun, Haolin; Qi, Yanfei
Abstract: Azo dyes in food, especially the illegal additives, have proved adverse effects on human health. It is important to establish high sensitivity, simple and fast sensors to monitor and analyze them in food. Herein, a sensitive electrochemical sensor using AuNPs/Zr-MOF-Graphene as the electrode modification material was established for detecting sunset yellow (SY) and Sudan I. The successfully prepared AuNPs/Zr-MOF-Graphene composites presented promising electrochemical sensing property toward SY and Sudan I due to their improving accumulation efficiency, electrocatalytic activity and promoting charge transfer. Under optimal conditions, the range of detection was 0.1–1000 μM and 0.1–800 μM with limit of detection (LOD) of 0.1 μM and 0.1 μM for SY and Sudan I, respectively. And the stability and repeatability were satisfactory. This simple and rapid electrochemical sensor displayed great performance for testing of SY in soft drink and Sudan I in chili powder, with a recovery of 92.89–109.87%, which would be a potential detection method for azo dyes. Highlights: The AuNPs/Zr-MOF-Graphene composites are successfully synthesized. The prepared AuNPs/Zr-MOF-Graphene composites exhibited promising electrochemical sensing property toward sunset yellow and Sudan I. LOD (0.1 μM) and wide detection range (0.1–1000 μM and 0.1–800 μM) were obtained.